(untitled) (Journal of Pakistan Orthopaedic Association, 2013)
Objective: To present extreme physical activity in military personnel can lead to a torn anterior cruciate ligament. Study design: Retrospective descriptive Study Place and duration of study: Rawalpndi and Multan 9 years period Method: We evaluated the results of 1577 personnel (patients) over a nine year period who sustained an acute injury to the knee joint while doing assault course training. 1278 (81%) of these injuries occurred while crossing a 9ft wide ditch (Figure 1). Results: 759 (48%) were anterior cruciate ligament tears either alone or in combination with a medial or lateral meniscus injury. The patients were initially evaluated by a brief trauma history as well as clinical examination; a further cohort underwent arthroscopy. Conclusion: We concluded that improving preventive measures in the form of better training during assault course as well as increasing clinical awareness amongst the medical officers dealing with these injuries initially, will improve the management outcome. There was also a need to further improve the training of the orthopaedic surgeons so that arthroscopic ACL repairs in carefully selected patients will help in overcoming this challenging knee injury. Keywords: Assault Course Training; Haemarthrosis; Anterior Cruciate Ligament; Prolonged Disability